Pemikiran Abu Al-A’al Al-Maududi - Barsihannor Annur (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
Sayyid Abu al-A’la Maududi was a prominent leader and important figure in Islamic resurrection in the 20 century. His Islamic thought became the keypoint of Islamic thought development. His works greatly influenced many scholars in many countries. Maududi had idea to make Islam as state ideology based on tauhid foundation. The sovereignity according to him absolutely belongs to God, people are just the executor of the sovereignity. Through this system, there will be the balance of life either in economic or sosio-politic. Economical system in Maududi’s thought must be balanced and aimed at making prosperity in society while the political system must refer to syariah.